Setting sails to sundry shores; Transnational memories of the Netherlands East Indies in the eyes of Danish writer Aage Krarup Nielsen - Arps, Arnoud (UI Scholars Hub, 2024)
The Danish travel writer Aage Krarup Nielsen (1891-1972) journeyed to the Netherlands East Indies on multiple occasions. Even though his translated work was popular in the Netherlands and beyond, so far it has been paid scant attention in the fields of travel-writing studies and the study of Netherlands Indies literature. Yet, it is valuable in its views on transnational power dynamics within the Netherlands East Indies society. This article examines two distinct patterns in Krarup Nielsen’s 1928 travelogue, Mellem kannibaler og paradisfugle (Between cannibals and birds of paradise): the comparisons he makes between the different ethnicities and nationalities who lived in the Netherlands East Indies and the memories he includes in the descriptions of his travels. Analysing this travel account from within the framework of postcolonial studies and transnational memory studies, this article answers the question how encounters with the “Other” – colonized as well as colonizer – are represented in the Netherlands East Indies. Drawing on earlier work describing representations by colonialists in “their” colony, this article focuses on the outsider perspective offered by Krarup Nielsen and takes into account how his European background shaped his descriptions of the “Others”.